Efektivitas Trichoderma sp. dan Gliocladium sp. untuk Pengendalian Penyakit Busuk Batang (Fusarium Oxysporum Sp.) pada Tanaman Vanili (Vanilla Planifolia) - PARDEDE, MEI NOVITA BR; WIRYA, GUSTI NGURAH ALIT SUSANTA; KALIMI, KHAMDAN (Agrotrop : Journal on Agriculture Science; Vol 12 No 1 (2022)DO - 10.24843/AJoAS.2022.v12.i01.p06, 2022)
Effectiveness of Trichoderma sp. and Gliocladium sp. For Controlling Stem Rot ( Fusarium Oxysporum sp.) in Vanilla ( Vanilla planifolia ) . Vanilla ( Vanilla planifolia Andrews) is one of the industrial plants that have very high economic value as an export commodity. One of the main obstacles to increasing vanilla production is stem rot disease. Stem rot disease caused by Fusarium oxysporum f. sp. vanillae became one of the main obstacles faced. This research on the effectiveness of antagonistic microbes aims to obtain the best antagonist microbes in suppressing stem rot disease in vanilla plants. The experiment was carried out in vitro at the Laboratory of Plant Diseases at Udayana University and in vivo at the Experimental Garden Greenhouse. The experiment used a randomized block design with six replications and four treatments, namely Control (without antagonistic microbes), G ( Gliocladium sp. + compost), T ( Trichoderma sp. + compost), and GT ( Gliocladium sp. and Trichoderma sp. + compost). The results showed that T ( Trichoderma sp. + compost) and GT ( Gliocladium sp. and Trichoderma sp. + compost) able inhibit stem rot disease with the best percentage of 10%.